Exhibition of dreams - Koncz, Linda (2022)
I recorded two thousand interviews with people describing what they had dreamt at night while they were sleeping. Then, I invited local artists of Lisbon - painters, animation artists, and performance artists - to create an exhibi- tion where the dreams were used as inspiration for the art-works. Dreaming and making art come from a similar origin; one is an unconscious action of creation, and the other is a conscious creative process. Interdisciplinary Dream exhibi- tions can blur the border between these different ways of creation, they can fade the hierarchy between the dreamer, the artist and the visitor. This empirical experiment offers a new, horizontal hierarchy between the dreamer, the artist and the viewer. The paper describes the uniqueness of the Dreampire exhibitions and their specific method in which dream reports serve as inspiration for the art pieces of different disciplines and suggests revision of the view on the relationship between culture and dreams.